Computational aspects in uncertainty estimation by Monte Carlo Method (INNOTEC, 2013)
The purpose of this paper is to analyze the various aspects related to the development of a software application aimed to uncertainty estimation by Monte Carlo Method, independent from worksheet or third party applications, such as MSExcel, MathLab or R. Difficulties and their available solutions around the needed stages to achieve this goal are discussed, as well as the algorithms needed for creating a math equations parser, the pseudo-random numbers generators with main probability distributions found in uncertainty calculations, and the management of Type A uncertainties.The application developed is tested on three samples: Air density determination according to CIPM equation, the pressuregenerated by a Pressure Balance and the standardizing of a solution of sodium hydroxide as in example A2 of EURACHEM/CITEC CG 4 guide. Finally, these results are compared with the results obtained applying the classical method (GUM) and those obtained using R software.
Keywords: Metrology; Uncertainty; Monte Carlo; Software; GUM; source code; Delphi